1997
DOI: 10.1152/physiologyonline.1997.12.2.78
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cardiac KATP Channels During Anoxia and Ischemia

Abstract: In isolated heart cells, maintained anoxia causes a transient opening of KATP channels. In the ischemic myocardium, this extra K+ conductance results in a decreased contractility and may be arrhythmogenic. Recent studies provide further evidence that the transient activity of KATP channels during anoxia is correlated with the time course of extracellular K+ accumulation during ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
4

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
2
0
4
Order By: Relevance
“…Changes in cellular metabolic status resulting from hypoxic or ischaemic conditions are well known to modulate ion channel activity in cardiac and other tissues, for example through altered channel phosphorylation state (Allen & Orchard, 1987; Trautwein & Hescheler, 1990; McDonald et al 1994; Benndorf et al 1997). However, in recent years several studies using a diverse range of tissues have indicated that ion channels are rapidly influenced by local oxygen levels in a membrane‐limited, possibly direct manner (reviewed by Peers, 1997).…”
mentioning
confidence: 99%
“…Changes in cellular metabolic status resulting from hypoxic or ischaemic conditions are well known to modulate ion channel activity in cardiac and other tissues, for example through altered channel phosphorylation state (Allen & Orchard, 1987; Trautwein & Hescheler, 1990; McDonald et al 1994; Benndorf et al 1997). However, in recent years several studies using a diverse range of tissues have indicated that ion channels are rapidly influenced by local oxygen levels in a membrane‐limited, possibly direct manner (reviewed by Peers, 1997).…”
mentioning
confidence: 99%
“…SURs are the binding sites for known blockers (e.g., glibenclamide) and activators (e.g., pinacidil and cromakalim) of these channels, which have found valuable therapeutic uses. K ATP channels are classically identified as being inhibited by intracellular ATP and were first described in cardiac myocytes (Noma, 1983) in which they were believed to act under conditions of metabolic stress to shorten action potential durations and so reduce the energy demands of myocytes when intracellular ATP levels are reduced (Benndorf et al, 1997).…”
mentioning
confidence: 99%
“…Àêòèâàö³ÿ ÀÒÔ-÷óòëèâèõ êà볺âèõ (Ê ÀÒÔ ) êàíàë³â êë³òèííèõ ìåìáðàí º îäíèì ³ç ãîëîâíèõ åíäîãåííèõ çàõèñíèõ ìåõàí³çì³â îðãàí³çìó â â³äïîâ³äü íà çìåíøåííÿ âíóò-ð³øíüîêë³òèííîãî âì³ñòó ÀÒÔ íèae÷å â³ä ì³ë³ìîëÿðíèõ ð³âí³â, çîêðåìà ïðè ã³ïîêñ³¿ òà ³øå쳿 òêàíèíè [22,31]. ¯õ åêçîãåííà àêòèâàö³ÿ ôàðìàêîëîã³÷íèì øëÿõîì çàïóñêຠíå ìåíø ïîòóaeí³, àíàëîã³÷í³ äî åíäîãåííèõ, çàõèñí³ ìåõàí³çìè, îäíèì ³ç ÿêèõ º çìåíøåííÿ âõîäó Ñà 2+ â êë³òèíó ÷åðåç L-òèï êàëüö³ºâèõ êàíàë³â [20,25], à òàêîae íàêîïè÷åííÿ éîãî â ìàòðèêñ³ ì³òîõîíäð³é âíàñë³äîê ïðèãí³÷åííÿ âõîäó ÷åðåç ïîòåí-ö³àëçàëåaeíèé êàëüö³ºâèé óí³ïîðòåð [26,29].…”
Section: âñòóïunclassified
“…¯õ åêçîãåííà àêòèâàö³ÿ ôàðìàêîëîã³÷íèì øëÿõîì çàïóñêຠíå ìåíø ïîòóaeí³, àíàëîã³÷í³ äî åíäîãåííèõ, çàõèñí³ ìåõàí³çìè, îäíèì ³ç ÿêèõ º çìåíøåííÿ âõîäó Ñà 2+ â êë³òèíó ÷åðåç L-òèï êàëüö³ºâèõ êàíàë³â [20,25], à òàêîae íàêîïè÷åííÿ éîãî â ìàòðèêñ³ ì³òîõîíäð³é âíàñë³äîê ïðèãí³÷åííÿ âõîäó ÷åðåç ïîòåí-ö³àëçàëåaeíèé êàëüö³ºâèé óí³ïîðòåð [26,29]. Îñíîâíèì åíäîãåííèì ðåãóëÿòîðîì àêòèâ-íîñò³ öèõ êàíàë³â º âíóòð³øíüîêë³òèííà êîíöåíòðàö³ÿ ÀÒÔ ³ äåêîëè, ÿê ó ïàíê-ðåàòè÷íèõ β-êë³òèíàõ, ãîëîâíó ðîëü â³ä³ãðຠñï³ââ³äíîøåííÿ ÀÒÔ/ÀÄÔ [22,33]. ¯õ çíà÷èì³ñòü â óìîâàõ ô³ç³îëîã³÷íî¿ íîðìè äëÿ á³ëüøîñò³ òêàíèí äîñ³ çàëèøàºòüñÿ íåâ³äîìîþ, òîä³ ÿê äëÿ ï³äøëóíêîâî¿ çàëîçè âîíà ïåâíèì ÷èíîì ðîçêðèòà.…”
Section: âñòóïunclassified
See 1 more Smart Citation